Toxoplasma gondii, Neospora caninum and Encephalitozoon cuniculi in Animals from Captivity (Zoo and Circus Animals) - Marková, Jiřina; Machačová, Tereza; Bártová, Eva; Sedlák, Kamil; Budíková, Marie; Silvestre, Pasquale; Laricchiuta, Paolo; Russo, Marco; Veneziano, Vincenzo (The Journal of eukaryotic microbiology, 2019)
Problems with parasitic infections are common in zoological gardens and circuses. In some animals it can lead to several disorders such as systemic disease, reproductive disorders (abortions and neonatal mortality), and even to death if severe illness is untreated. Thus, the aim of this study was to evaluate the prevalence of three common parasites in 74 animals from three zoos, and four circuses in Southern Italy. Antibodies to Toxoplasma gondii, Neospora caninum, and Encephalitozoon cuniculi were detected in 51%, 12%, and 20% of animals, respectively. Co-infections of T. gondii and N. caninum were reported in seven animals (9%) and co-infection of T. gondii and E. cuniculi in one animal. T. gondii, N. caninum and E. cuniculi seroprevalence differed in type of diet (P ≤ 0.0001; P ≤ 0.037 and P ≤ 0.004, respectively). T. gondii and E. cuniculi seroprevalence also differed in animal families (P ≤ 0.0001) and according to type of housing (P ≤ 0.003), respectively. Statistical differences were not found in other characteristics (gender, age, country of birth, origin, and contact with cats or dogs). This is the first serological study focusing on protozoan and microsporidian parasites in zoo and circus animals from Southern Italy and the first detection of antibodies to E. cuniculi in camels in Europe.
Keywords: savci; exotic animals; Coccidiosis; kokcidióza; zvířata v ZOO; prevalence; toxoplasmosis; Itálie; Female; serology; encephalitozoonóza; séroepidemiologické studie; zvířata; Mammals; Neospora; Encephalitozoonosis; ženské pohlaví; Toxoplasma; Animals, Zoo; Male; toxoplazmóza zvířat; Encephalitozoon cuniculi; Prevalence; Animals; Toxoplasmosis, Animal; Italy; mužské pohlaví; neosporosis; Seroepidemiologic Studies